Security Surveillance Architecture: The Wireless Mesh Network Approach - Ogunyinka , O.I.; Soyemi, J.; Soyemi, O. B. (Mediterranean Journal of Social Sciences, 2011)
The state of security in the country had been created a lot of panic in many areas to the extent that individuals nowsend a lot to protect their lives and properties. This state had not justified to a large extent the huge amount the government hadspent, presently spending and had budgeted to spend in the present year on providing adequate security for her citizenry. Evenat the state level we hear and see several donations running into millions of naira made by state governors to the police forcejust to increase the level of security in the state. However, all these had been geared towards improving the physical capability ofthe police force and other security agents rather than improving the technological infrastructure through the use of InformationTechnology to create a nationwide video-surveillance security system. A Security Surveillance Architecture will be proposed inthis paper, and it is believed that it will go a long way in alleviating the security problems of our nation.